Genetic Basis of Tillering Angle from Other Plants to Wheat: Current Progress and Future Perspectives - Xiaohong Chen; Tingshu Lei; Yuming Yan; Mengyu Sun; Tao Zhong; Baolin Wu; Hanxi Liu; Chao Zhang; Fengli Sun; Yajun Xi (Plants)
Plant architecture is an important agronomic trait that impacts crop yield. The tiller angle is a critical aspect of the plant’s structural organization, which is influenced by both internal and external factors. The genetic mechanisms underlying the tiller angle have been extensively investigated in other plants. However, research on wheat is relatively limited. Additionally, mechanics has emerged as a connection between biochemical signaling and the development of three-dimensional biological forms. It not only reveals how physical interactions at the cellular level influence overall morphogenesis but also elucidates the interplay between these mechanical processes and molecular signaling pathways that collectively determine plant morphology. This review examines the recent advancements in the study of tillering angle in wheat and other plants. It discusses progress in research ranging from observable characteristics to the regulation of genes, as well as the physiological and biochemical aspects, and the adaptability to environmental factors. In addition, this review also discusses the effects of mechanical on plant growth and development, and provides ideas for the study of mechanical regulation mechanism of tillering angle in wheat. Consequently, based on the research of other plants and combined with the genetic and mechanical principles, this approach offers novel insights and methodologies for studying tillering in wheat. This interdisciplinary research framework not only enhances our understanding of the mechanisms underlying wheat growth and development but may also uncover the critical factors that regulate tillering angle, thereby providing a scientific foundation for improving wheat yield and adaptability.